1997
DOI: 10.2307/3870429
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Naphthylphthalamic Acid Binding in the tir3 Mutant of Arabidopsis Is Associated with a Reduction in Polar Auxin Transport and Diverse Morphological Defects

Abstract: Polar auxin transport plays a key role in the regulation of plant growth and development. To identify genes involved in this process, we have developed a genetic procedure to screen for mutants of Arabidopsis that are altered in their response to auxin transport inhibitors. We recovered a total of 16 independent mutants that defined seven genes, called TRANSPORT INHIBITOR RESPONSE (TIR) genes. Recessive mutations in one of these genes, TIR3, result in altered responses to transport inhibitors, a reduction in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
121
1
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(130 citation statements)
references
References 0 publications
6
121
1
2
Order By: Relevance
“…The mutant displays an NPAresistant phenotype similar to other tir mutants, such as tir1 and tir3 (Ruegger et al, 1997). When grown on 5 mM NPA, wild-type seedlings exhibited approximately 60% root elongation after 3 d compared to untreated controls, while tir2-1 seedlings displayed 75% root elongation (Fig.…”
Section: The Tir2 Mutant Exhibits An Altered Response To Npa But Not mentioning
confidence: 91%
See 2 more Smart Citations
“…The mutant displays an NPAresistant phenotype similar to other tir mutants, such as tir1 and tir3 (Ruegger et al, 1997). When grown on 5 mM NPA, wild-type seedlings exhibited approximately 60% root elongation after 3 d compared to untreated controls, while tir2-1 seedlings displayed 75% root elongation (Fig.…”
Section: The Tir2 Mutant Exhibits An Altered Response To Npa But Not mentioning
confidence: 91%
“…Thus, mutants that are resistant to NPA may have defects in synthesis, transport, or response because roots of these mutants are expected to have lower levels of IAA or reduced sensitivity to IAA. This screen succeeded in isolating mutations in seven genes with weak NPAresistant phenotypes, including genes related to auxin signaling (TIR1), auxin transport (TIR3), and auxin synthesis (TIR7; Ruegger et al, 1997Ruegger et al, , 1998Ljung et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent series of highly ordered transverse cell divisions leads to the emergence of the newly formed lateral root (Malamy and Benfey, 1997). Numerous studies have shown that auxin, and in particular its polar transport, is necessary for the initiation and the later development of lateral roots (Ruegger et al, 1997;Reed et al, 1998;Casimiro et al, 2001). The initiation phase of lateral root development is dependent on basipetal polar auxin transport and can be blocked by the auxin transport inhibitor N-1-naphthylphthalamic acid (Casimiro et al, 2001).…”
Section: Cytokinins Are a Regulatory Factor In Root Branchingmentioning
confidence: 99%
“…The endogenous auxin IAA does not compete with NPA for this binding site (Lomax et al, 1995). In the tir3 mutant of Arabidopsis, reduced NPA binding is associated with defects in auxin-regulated growth processes, suggesting that the NPA-binding site is important for auxin transport (Ruegger et al, 1997).…”
mentioning
confidence: 99%